Effect of feeding maize silage containing Moringa (Moringa oleifera) leaves on growth, blood metabolites, serum antioxidant and coccidial egg count in Barbari goats under stall-fed condition - KUMAR, RAVINDRA; SHARMA, D K; SWAROOP, K; ARIF, MOHD. (The Indian Journal of Animal Sciences, 2022)
Feeding cum growth trial was conducted on male Barbari goats to study the growth, blood metabolites, antioxidant and coccidial egg count on feeding of Maize silage having Moringa leaves. Eighteen male Barbari goats (Aged about 3 months and Avg B.Wt. 9.53±0.42 kg) were divided in completely randomized design into (CRD) three groups of six each. Control group (Gr C) was fed with concentrate pellet, green and gram straw ad lib. Treatment groups (Gr M) were fed with concentrate pellet + maize silage ad lib.; Gr MM was fed with concentrate pellet + Maize –Moringa silage ad lib. Average daily gain (g/day) was highest in Gr MM (71.42) followed by Gr M (60.87) and Gr C (55.31). There was no significant difference in hematological and serum metabolites (Glucose, total protein, albumin, globulin, AG ratio) among groups. Serum cholesterol (mg/dl) was significantly lower in Gr MM as compared to Gr M and Gr C. There was improvement in the serum antioxidant activity of the goats fed with MM silage. Present study concluded that incorporation of Moringa olifera in the maize silage improved the body weight gain with reduction in serum cholesterol in growing Barbari goats under stall feeding system.